Respuesta :

Hello !

Answer:

When x = -3 or x = 3

Step-by-step explanation:

[tex] \frac{ {x}^{2} - 9}{ {x}^{2} + 6x + 8} = 0[/tex]

[tex]\Leftrightarrow \frac{ {x}^{2} - 9 }{ {x}^{2} + 6x + 8} \times ( {x}^{2} + 6x + 8) = 0 \times ( {x}^{2} + 6x + 8)[/tex]

[tex]\Leftrightarrow {x}^{2} - 9 = 0[/tex]

[tex]\Leftrightarrow(x - 3)(x + 3) = 0[/tex]

[tex]\Leftrightarrow \: x - 3= 0 \: or \: x + 3 = 0[/tex]

[tex]\Leftrightarrow \: x = 3 \: or \: x = - 3[/tex]

[tex]\boxed{S = {-3 \: \: or \: \: 3}}[/tex]